2017
DOI: 10.1083/jcb.201612018
|View full text |Cite
|
Sign up to set email alerts
|

Selective aggregation of the splicing factor Hsh155 suppresses splicing upon genotoxic stress

Abstract: Alterations of the transcriptome and proteome enable stress recovery, but coordination of these events under stress is only partly understood. Mathew et al. report that under stress, an RNA splicing complex disassembles and the splicing factor Hsh155 moves to protein aggregates, coinciding with a drop in splicing and concomitant repression of ribosome production.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(35 citation statements)
references
References 51 publications
2
33
0
Order By: Relevance
“…In a concerted effort to maintain genome integrity, the DDR pathway plays a critical role in sensing DNA damage and orchestrating the repair of ensuing DNA lesions [7577]. This recovery process typically involves global remodeling of both the transcriptome and the proteome [7880]. However, an implicit assumption in this thinking is that most cells return to their initial transcriptional and proteomic state following DNA damage and repair, aside from those that may acquire a mutation.…”
Section: Introductionmentioning
confidence: 99%
“…In a concerted effort to maintain genome integrity, the DDR pathway plays a critical role in sensing DNA damage and orchestrating the repair of ensuing DNA lesions [7577]. This recovery process typically involves global remodeling of both the transcriptome and the proteome [7880]. However, an implicit assumption in this thinking is that most cells return to their initial transcriptional and proteomic state following DNA damage and repair, aside from those that may acquire a mutation.…”
Section: Introductionmentioning
confidence: 99%
“…INQ formation is driven by the small heat shock protein Hsp42, and the aggregase protein Btn2 (13), while INQ dissolution is regulated by Hsp104 and the Hsp70 system (9,11,12). Here we show that Cdc48 is also a stress-inducible component on INQ structures and that it plays an enzymatic role in INQ turnover.…”
Section: Introductionmentioning
confidence: 69%
“…Sfp1 is well characterized for its role in adjusting cell size and ribosome production during stress 5355,76,77 , yet its functions outside the control of ribosome biogenesis are understudied. Recently, Matthew et al found that sequestration of the splicing factor Hsh155 during genotoxic stress was regulated via TORC1 signaling through Sfp1 93 . Together with our data showing that Sfp1 regulates TRA1 expression, this study supports an expanded role for Sfp1 in stress response, beyond regulating ribosome biogenesis.…”
Section: Discussionmentioning
confidence: 99%